UPAYA MENINGKATKAN MOTIVASI KERJA MELALUI SUPERVISI AKADEMIK PADA GURU SD DI KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Rolialis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research is a school action research conducted at the Lubuk Batu Jaya District Elementary School in Indragiri Hulu Regency. The population in this study were all elementary school teachers in the Lubuk Batu Jaya Subdistrict, Indragiri Hulu Regency, amounting to 60 people. The problem behind this research is the low motivation of teacher work in the primary schools of the Lubuk Batu Jaya Subdistrict, Indragiri Hulu Regency. The purpose of this study is to increase themotivation of working teachers. The results of the study prove that, the number of assessment scores on pre-cycle is 894 with an average of 62.08 sufficient categories, in the first cycle, the number of scores increases to 1057 with an average of 73.40 good categories, and in cycle II the number of scores in cycle II increases 1210 with an average of 84.02 very good categories. Based on the results of this study it can be concluded that through academic supervision it can improve the motivation of the work of the Lubuk Batu Jaya District Elementary School teachers in Indragiri Hulu Regency.